Flexible and stretchable triboelectric nanogenerator fabric for biomechanical energy harvesting and self-powered dual-mode human motion monitoring. (August 2021) - He, Meng; Du, Wenwen; Feng, Yanmin; Li, Shijie; Wang, Wei; Zhang, Xiang; Yu, Aifang; Wan, Lingyu; Zhai, Junyi
Abstract: Simultaneous monitoring of human motion and collecting ambient energy are important for the development of personal healthcare monitoring and artificial intelligence. Here, a flexible and stretchable coaxial triboelectric nanogenerator (TENG) yarn is designed and fabricated by using coil spring as the inner support layer and mechanoluminescent ZnS:Cu/PDMS composite as the outer friction layer. By weaving coaxial TENG yarns, or mix-weaving with other yarns, a multifunctional TENG fabric can be manufactured for energy harvesting external mechanical energy from human motion or ambient environment. More important, it can self-powered sense human motion in both electrical (through TENG) and optical (from mechanoluminescent ZnS:Cu/PDMS composite) methods. This work provides a new strategy for wearable TENG fabrics with dual-mode sensing and energy harvesting which have potential applications in long-term medical monitoring and human-machine interaction systems. Graphical Abstract: A multifunctional triboelectric nanogenerator fabric is manufactured for energy harvesting external mechanical energy from human motion or ambient environment. Moreover, on the basis of coupling effects between the mechanical luminescence and triboelectrification important, it can self-powered sense human motion in both electrical (through TENG) and optical (from mechanoluminescent ZnS: Cu/PDMS composite) methods. ga1 Highlights: The wearable fiber is fabricated for energy harvesting and monitoring human signals in medical rehabilitation. A dual-mode strain sensor is designed by triboelectricity and mechanoluminescence. A fiber-shaped sensor possesses mechanical luminescence performance, which can sense the force variation more intuitively. The triboelectric fiber exhibit good washing resistance and reusability.